PENYULUHAN HUKUM MENGENAI BENTUK-BENTUK BADAN USAHA BAGI UMKM MENURUT UNDANG-UNDANG NOMOR 20 TAHUN 2008 KEPADA ANGGOTA KARANG TARUNA KELURAHAN MERANTI PANDAK KOTA PEKANBARU - Hasnati Hasnati; Sandra Dewi; Andrew Shandy Utama; Laila Shafira; Widya Andri (Ensiklopedia Research and Community Service Review, 2021)
The problem with partners in this community service activity is the lack of knowledge of Karang Taruna members, Meranti Pandak Village, Rumbai District, Pekanbaru City regarding forms of business entities for Micro, Small and Medium Enterprises (MSMEs) based on Law Number 20 of 2008 concerning Business. Micro, Small, and Medium. The solution offered in this community service activity is to increase the knowledge of Karang Taruna members, Meranti Pandak Village, Rumbai District, Pekanbaru City regarding forms of business entities for Micro, Small and Medium Enterprises (MSMEs) based on Law Number 20 of 2008 concerning Micro Enterprises. , Small, and Medium. The implementation method used in this community service activity is to use the lecture, dialogue, and discussion methods in order to provide legal counseling. Partners' participation in this community service activity is by providing time, providing a place and its supporting facilities, and presenting members as activity participants. The output target of this community service activity is scientific articles published in the Sinta-5 accredited national journal. The conclusion of this community service activity is that this activity has been successfully implemented and the benefits can be felt directly by the participants. Before the activity was carried out, of the 15 participants, only 29.3% answered that they knew about the material to be delivered. Meanwhile, after the activity was carried out, 77.3% of participants answered that they knew the material presented.Keywords: Law; MSMEs; Legal entity.